Comparative Study of Glucose and Xylose Production in Enzymatic Hydrolysis Result by Batch and Fed Batch Method - Silvia Oktavia Nur Yudiastuti; Efri Mardawati; MTAP Kresnowati; Yazid Bindar (Fakultas Teknologi Industri Pertanian, 2018)
Xylose is a five carbon chain monosaccharide that can be used as a substrate in the fermentation of low-calorie xylitol. While glucose is a six carbon chain monosaccharide that can be processed into glucose syrup as a more stable natural sweetener in the food processing industry. Xylose is xylan monomer produced from hydrolysis of hemicellulose from plants or biomass woody waste. While glucose is the result which is also produced in xylan hydrolysis by xylanase enzymatic hydrolysys. In the search for the source of hemicellulose, oil palm empty fruit bunch (OPEFB) as a solid waste from crude palm oil processing is a source that can be utilized in this research. OPEFB waste is abundant by the increasing world demand for vegetable oil. Considering the OPEFB enzymatic hydrolysis was a hetrogenous solid-liquid reaction, fed batch feeding of substrate was thought to improve the reaction performance. Hydrolysis experiments were performed at temperature 500C, pH 5 and for 96 hours hydrolysys time with substrate concentration at 15% and enzyme dose of 1%. The result showed that the feed-batch hydrolysis configuration provided higher yield of xylose and glucose than batch configuration but unsignificant.Keywords : Enzymatic Hydrolysis, Fed-batch, glucose, Xylan, Xylanase, Xylose.